The Effect of Feeding Time in Toddlers on Stunting in Indonesia: Systematic Review - Verawati Agustien; Mariyani Mariyani (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Stunting is a disorder of growth and development experienced by children as a long-term manifestation of malnutrition and recurrent infections. Previous research has shown that one of the problems in infant feeding is the cessation of breastfeeding and insufficient breastfeeding. The purpose of this study was to conduct a systematic study on the effects of premature breastfeeding on the incidence of stunting in Indonesia. This study was conducted by systematic review. Research data is sought from several indexing including: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords "complementary feeding AND Stunting", "supplementary feeding AND stunting", "complementary feeding AND children aged 6-24 months AND Stunting", "feeding time AND stunting AND children under 5 years". The results of the study to be selected are in the period 2018-2023. The review reported that 9 out of 10 articles had cited a significant association of premature breastfeeding MP with an increase in stunting incidence with the resulting odds ratio ranging from 1.6 to 8 times.